Hubungan Kualitas Pelayanan Dan Peran Perawat Terhadap Kepuasan Pasien - Sena Wahyu Purwanza; Icca Presilia Anggreyanti; Catur Wibowo (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: to analyze the relationship between service quality and the role of nurses in patient satisfactionMethods: The design of this study used descriptive analytics with a cross-sectional approach. The sample used is 55 respondents using the purposive sampling technique. The research instrument used was a questionnaire on service quality and the role of nurses which had been tested for validity with an r table value of 0.852 > 0.444 and a Cronbach alpha reliability test of 0.909 > 0.600, which means that all instruments were declared valid and reliable. Data analysis used a chi-square statistical test.Results: The results showed a p-value of 0.001 (p < 0.05), which means that the quality of service and the role of nurses are related to patient satisfaction.Conclusion: The conclusion of this study is that the quality of service and the role of a good nurse will be related to the level of patient satisfaction to improve the quality of nursing services.